Preclinical evaluation of the Versius surgical system: A next‐generation surgical robot for use in minimal access prostate surgery - Nikhil Vasdev; Philip Charlesworth; Mark Slack; Jim Adshead (BJUI Compass, 2023)
Abstract Objectives To evaluate the Versius surgical system for robot‐assisted prostatectomy in a preclinical cadaveric model using varying system setups and collect surgeon feedback on the performance of the system and instruments, in line with IDEAL‐D recommendations. Materials and methods Procedures were performed in cadaveric specimens by consultant urological surgeons to evaluate system performance in completing the surgical steps required for a prostatectomy. Procedures were conducted using either a 3‐arm or 4‐arm bedside unit (BSU) setup. Optimal port placements and BSU layouts were determined and surgeon feedback collected. Procedure success was defined as the satisfactory completion of all steps of the procedure, according to the operating surgeon. Results All four prostatectomies were successfully completed; two were completed with a 3‐arm BSU setup and two using a 4‐arm BSU setup. Small adjustments were made to the port and BSU positioning, according to surgeon preference, in order to complete the surgical steps. The surgeons noted some instrument difficulties with the Monopolar Curved Scissor tip and the Needle Holders, which were subsequently refined between the first and second sessions of the study, in line with surgeon feedback. Three cystectomies were also successfully completed, demonstrating the capability of the system to perform additional urological procedures. Conclusions This study provides a preclinical assessment of a next‐generation surgical robot for prostatectomies. All procedures were completed successfully, and port and BSU positions were validated, thus supporting the progression of the system to further clinical development according to the IDEAL‐D framework.